Oil Filter Machine for Deep Frying with Smartphone Control and Monitoring using Client-Server Communication Protocol - Ramadhan, Aditya; Nurdin, Ali; Suroso, Suroso (Program Studi Teknik Elektro Universitas Khairun, 2024)
The prevalence of fried snack consumption in our surroundings has become a widespread phenomenon. These fried snacks, commonly relished by many, are frequently served as side dishes with our main meals and are also a popular choice for satisfying quick hunger cravings. By utilizing the client-server communication method, this device can be assisted in its operation. The device employs ESP8266 as both the transmitter and receiver, while a smartphone serves as the control and monitoring tool. The primary purpose of this setup is to enhance the efficiency of oil-based food consumption, promoting healthier habits. The data collected from the device is split into two categories. Firstly, the communication data consists of the average RSSI (-52dBm) measured at a distance of 1 meter, with RSSI values increasing and becoming more susceptible as the distance grows. Secondly, the machine was tested for oil drainage in food, resulting in a weight decrease of 2.6% after 60 seconds of device usage, and the percentage of weight reduction increased with the given time.